2009
DOI: 10.1016/j.febslet.2009.09.052
|View full text |Cite
|
Sign up to set email alerts
|

Cell sex determines anoikis resistance in vascular smooth muscle cells

Abstract: a b s t r a c tSexual dimorphism, detectable in vascular smooth muscle cells freshly isolated from aorta of male and female rats, is associated with a different susceptibility to radiation-induced apoptosis. In this work we investigated the mechanism underlying this difference and discovered that, in comparison with cells from male rats, cells from female rats show adhesion-associated resistance to apoptosis, the so called anoikis resistance. This is apparently due to a more adhering phenotype, characterized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 28 publications
(43 reference statements)
3
36
1
Order By: Relevance
“…However, slight variations in the intracellular redox environment and in the detoxification machinery can have profound effects on a number of intracellular signaling molecules, thereby modifying cell functions and cell fate. In this context, it was recently suggested that ROS production and detoxification machinery are sex-gender dependent and that XX and XY cells have a determining role in the response to oxidative insults Straface et al, 2009). In particular, the basal differences in the redox state of freshly isolated cells from males and females indicate that XX cells have higher GSH content and that this can provide these cells with greater protection from oxidants (see below) .…”
Section: Cytology and Cytopathology In Male And Female Cells 721 Omentioning
confidence: 96%
“…However, slight variations in the intracellular redox environment and in the detoxification machinery can have profound effects on a number of intracellular signaling molecules, thereby modifying cell functions and cell fate. In this context, it was recently suggested that ROS production and detoxification machinery are sex-gender dependent and that XX and XY cells have a determining role in the response to oxidative insults Straface et al, 2009). In particular, the basal differences in the redox state of freshly isolated cells from males and females indicate that XX cells have higher GSH content and that this can provide these cells with greater protection from oxidants (see below) .…”
Section: Cytology and Cytopathology In Male And Female Cells 721 Omentioning
confidence: 96%
“…Not only are males more at risk due to androgens, it now appears that SMCs from female donors are more resistant to apoptosis [16]. The observations were made in the context of resistance to radiation injury, but the mechanism involves cell damage by reactive oxygen species, which has been implicated in AAA progression [17].…”
Section: Sex Differences In Susceptibility To Aortic Aneurysmsmentioning
confidence: 98%
“…Their results confirmed that number of detached cells in female were lower both prior to UV radiation and after radiation. 101 A series of studies have shown sex-dependent interactions between SMCs and nitric oxide (NO), a molecule known to inhibit the development of neointimal hyperplasia. 42,43 Hogg et al evaluated the efficacy of NO at inhibiting the vascular SMC proliferation, migration and cell cycle progression in vitro, as well as neointimal hyperplasia in vivo.…”
Section: Atherosclerosismentioning
confidence: 99%